High Performance Thin Layer Chromatography Method for Determination of Biotin in Edible Bird’s Nest - Teo, Peishan; Liu, Daicheng; Dai, Meixue (Asian Journal of Chemistry, 2012)
In the present study, we detected biotin in the edible bird's nest for the first time and determined the optimal extraction and biotin. The biotin was extracted using N,N-dimethylformamide. Separation of biotin was performed by using a mobile phase consisting of chloroform: acetone:methanol:glacial acetic acid (2.5:2.5:1:0.01, v:v:v:v) on precoated silica gel 60 F254 HPTLC plates. Densitometric evaluation of the spots was carried out in the absorbance wavelength at 400 nm. The spotting of the extract and standard solution is 0.47 of Rf value. The method was validated for precision, intra and interday and recovery. The relative standard deviation (RSD) precision was 1.22 % in 0, 2, 4 and 6 h. Intra and interday variation studies gave 0.56, 1.17, 0.78, 1.02, 1.66, 0.55, 0.46 and 1.03 RSD (£5 %) for the different concentration and time. Average recovery of 99.12 % was recorded and total content of biotin in edible bird's nest was 30.3 μg/g. Detection of biotin may also be an effective method to determine adulteration in edible bird's nest.